Design of Information Technology Governance in Educational Institutions Using COBIT 2019 Framework - Breindnaldo Vichario Tulus; Andeka Rocky Tanaamah (Universitas Bina Darma, 2023)
In the contemporary era, the role of information technology in the performance of organizations, institutions, and companies is of utmost importance. The implementation of information technology can effectively enhance decision-making efficiency and effectiveness. Educational institutions have been utilizing information technology to support their academic activities and business processes; however, the governance of this technology has never been audited before. This study aims to conduct an audit and analysis of information technology governance that employs the COBIT 2019 framework. The study's results suggest that educational institutions must improve risk and security management in the use of information technology and evaluate their business processes' implementation in accordance with the established regulations and requirements.